1971
DOI: 10.1136/pgmj.47.552.660
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction during pregnancy: report of two cases with a review of the literature

Abstract: Summary Two further cases of myocardial infarction during pregnancy are reported. From the review of the literature of forty-three cases of myocardial infarction during pregnancy and labour, it appears that myocardial infarction in the last trimester and labour is frequently fatal. Short-term anticoagulant therapy to suppress any thrombo-embolic tendency is desirable. Termination of pregnancy is indicated for patients in cardiac failure or persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Though they are seldomly seen, pregnant diabetics with ischemic heart disease are considered to run an extremely high risk (81,179). A maternal mortality of 30% is reported following myocardial infarction during pregnancy (93).…”
Section: Fig 3 Individual Maternal Mean Blood Glucose Concentrationmentioning
confidence: 99%
“…Though they are seldomly seen, pregnant diabetics with ischemic heart disease are considered to run an extremely high risk (81,179). A maternal mortality of 30% is reported following myocardial infarction during pregnancy (93).…”
Section: Fig 3 Individual Maternal Mean Blood Glucose Concentrationmentioning
confidence: 99%
“…As previously indicated, there have been numer-ous reports of pregnancy complicated by myocardial infarction (1,2,4,6,10,21,23,24). Mortality ranging from 0% in early pregnancy to 557 ( in late pregnancy has been cited (24).…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports of the morphology of the coronary arteries in acute myocardial infarction associated with pregnancy are rare. Reports of normal coronary arteries have been recorded following coronary arteriography (Sasse et al 1975) but triple vessel disease has also been reported in pathological studies (Husaini 1971). Our patient showed single vessel disease with a proximal anterior descending occlusion and the ventriculogram revealed a left ventricular aneurysm.…”
Section: Discussionmentioning
confidence: 99%